FAKTOR – FAKTOR YANG MEMPENGARUHI AKSEPTOR KB DALAM MEMILIH METODE KONTRASEPSI SUNTIK DI PRAKTIK MANDIRI BIDAN(PMB) ANNISA KOTA PRABUMULIH - Mandasari, Pera (LPPM STIKes Mitra Adiguna, 2024)
Injectable contraception is a contraceptive in the form of a liquid that is injected into a woman's body periodically and contains hormones, then enters the blood vessels to be absorbed little by little by the body which is useful for preventing pregnancy. The aim of the study was to find out the factors that influence family planning acceptors in choosing the injection contraceptive method at the Independent Midwife Practice (PMB) Annisa Prabumulih. The research method is analytic in nature, using a Cross Sectional approach. The population of this study were all active family planning acceptors at Annisa Prabumulih's Independent Midwife Practice (PMB). Sampling in this study using a total sampling technique, namely as many as 57 respondents. Research instruments in the form of checklists and questionnaires. The results of the study based on biivariate analysis there is a significant relationship between education and the choice of family planning injection contraception with a Pvalue of 0.000 <? 0.05, there is a significant relationship between knowledge and the choice of family planning injection contraception with a Pvalue of 0.000 <? 0.05, there is a significant relationship between husband's support and selection of contraceptive injections with a Pvalue of 0.001 < ? 0.05.